Paleoenvironments from robust loess stratigraphy using high-resolution color and grain-size data of the last glacial Krems-Wachtberg record (NE Austria). (15th November 2020) - Sprafke, Tobias; Schulte, Philipp; Meyer-Heintze, Simon; Händel, Marc; Einwögerer, Thomas; Simon, Ulrich; Peticzka, Robert; Schäfer, Christian; Lehmkuhl, Frank; Terhorst, Birgit
Abstract: The complex interplay of dust sedimentation, pedogenesis, and erosion/reworking in the formation of loess-paleosol sequences (LPS) challenges paleoenvironmental proxies. Here we show that color and grain size are essential parameters characterizing loess profiles and support robust stratigraphies as a basis for reconstructions in the context of local geo-ecological and large-scale paleoclimatic evolution. Detailed paleoenvironmental records from the period since the arrival of anatomically modern humans to the last glacial maximum are scarce in the Alpine surroundings. The c. 7.5 m thick LPS Krems-Wachtberg, NE Austria, known for its well-preserved Upper Paleolithic context at a depth of 5.5 m, formed between 40 and 20 ka BP by quasi-continuous dust-sedimentation, interrupted by phases of incipient pedogenesis and local reworking. The new KW2015 composite is based on three sections studied and sampled at 2.5 cm resolution. Color and grain size data support a robust stratigraphy for reconstructions of the pedosedimentary evolution. The marked transition from oxidized to reduced paleosols of KW2015 around 34–35 ka corresponds to the Middle-to Upper Pleniglacial transition as part of a general cooling trend from marine isotope stage (MIS) 3 to 2, intensely modulated by millennial-scale climatic fluctuations as recorded in the Greenland ice core data. The distinct response of KW2015 to these trends highlights that reconstructing LPS evolution based on a robust stratigraphy is a prerequisite to paleoenvironmental proxy interpretation. Highlights: 7.2 m thick loess studied at the Upper Paleolithic Krems-Wachtberg site (KW2015). Detailed KW2015 stratigraphy supported by high-resolution color and grain size data. Complex pedosedimentary evolution challenges standard paleoenvironmental proxies. Detailed Middle- to Upper Pleniglacial paleoenvironmental record in the NE Alpine forelands. Distinct local response of KW2015 to large-scale paleoclimatic shifts (MIS 3/2 transition).